General Practitioner's use of online resources during medical visits: managing the boundary between inside and outside the clinic. (10th October 2019) - Stevenson, Fiona; Hall, Laura; Seguin, Maureen; Atherton, Helen; Barnes, Rebecca; Leydon, Geraldine; Pope, Catherine; Murray, Elizabeth; Ziebland, Sue
Abstract: In an increasingly connected world, information about health can be exchanged at any time, in any location or direction, and is no longer dominated by traditional authoritative sources. We consider the ways information and advice given in consultations by doctors transcends the boundary between the clinic and the home. We explore how information that is widely accessible outside the consultation is transformed by General Practitioners (GPs) into a medical offering. Data comprise 18 consultations identified from 144 consultations between unselected patients and five GPs. We use conversation analytic methods to explore four ways in which GPs used online resources; (i) to check information; (ii) as an explanatory tool; (iii) to provide information for patients for outside the consultation; (iv) to signpost further explanation and self‐help. We demonstrate the interactional delicacy with which resources from the Internet are introduced and discussed, developing and extending Nettleton's (2004) idea of 'e‐scaped medicine' to argue that Internet resources may be 'recaptured' by GPs, with information transformed and translated into a medical offering so as to maintain the asymmetry between patients and practitioners necessary for the successful functioning of medical practice.